Application of magnetic solvent bar liquid-phase microextraction for determination of organophosphorus pesticides in fruit juice samples by gas chromatography mass spectrometry. (1st June 2015) - Wu, Lijie; Song, Ying; Hu, Mingzhu; Zhang, Hanqi; Yu, Aimin; Yu, Cui; Ma, Qiang; Wang, Ziming
Highlights: A novel MSB-LPME was first applied for determination of OPPs in juice samples. The MSB-LPME device was cheaply manufactured and easily assembled. The magnetic solvent bar can be used to stir and extract the analytes. This smart MSB can make the operation of sample treatment be simplified. The magnetic solvent bar is easier isolated from the sample. Abstract: A simple, rapid and sensitive sample pretreatment technique, magnetic solvent bar liquid-phase microextraction (MSB-LPME) was developed for extracting organophosphorus pesticides from fruit juice. The analytes were extracted from the sample to the organic solvent immobilized in the fiber. The magnetic solvent bar not only can be used to stir the samples but also extract the analytes. After extraction, the analyte-adsorbed magnetic solvent bar can be readily isolated from the sample solution by a magnet, which could greatly simplify the operation and reduce the whole pretreatment time. The bar was eluted with methanol. The elute was evaporated to dryness and residue was dissolved in hexane. Several experimental parameters were investigated and optimized, including type of extraction solvent, number of magnetic solvent bar, extraction temperature, extraction time, salt concentration, stirring speed, pH and desorption conditions. The recoveries were in the range of 81.3–104.6%, and good reproducibilities were obtained with relative standard deviation below 6.1%.